2009
DOI: 10.3997/1873-0604.2009025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of seawater intrusion using 2D electrical imaging

Abstract: Abstract. We have investigated the potential of 2D electrical imaging for the characterization of seawater intrusion using field data from a site in Almeria, SE Spain. Numerical simulations have been run for several scenarios, with a hydrogeological model reflecting the local site conditions. The simulations showed that only the lower salt concentrations of the seawater-freshwater transition zone could be recovered, due to the loss of resolution with depth. We quantified this capability in terms of the cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 48 publications
1
95
0
1
Order By: Relevance
“…5 shows that although the recovered conductive anomalies are located at depth, where ERT sensitivity and resolution is decreased, in particular the anomalies in the middle and in the NE part of the profile are still characterized by cumulative sensitivity values that allow a quantitative interpretation (e.g. Kemna 2000;Nguyen et al 2009). To explicitly prove that the conductive anomalies can be indeed recovered from the data, we inverted synthetic data computed from the obtained inversion result for the longitudinal profile.…”
Section: Geoelectrical Observationsmentioning
confidence: 99%
“…5 shows that although the recovered conductive anomalies are located at depth, where ERT sensitivity and resolution is decreased, in particular the anomalies in the middle and in the NE part of the profile are still characterized by cumulative sensitivity values that allow a quantitative interpretation (e.g. Kemna 2000;Nguyen et al 2009). To explicitly prove that the conductive anomalies can be indeed recovered from the data, we inverted synthetic data computed from the obtained inversion result for the longitudinal profile.…”
Section: Geoelectrical Observationsmentioning
confidence: 99%
“…It is non-invasive since it only requires electrodes at the ground surface. However, surface measurements suffer from poor resolution at depth [45,113,114] even if Robert et al [51] successfully managed to follow a salt tracer in fractures at a depth of 20 to 30 m. Hermans et al [74] propose guidelines deduced from their study case to design surface arrays for monitoring studies. Using 62 electrodes with an electrode spacing a, they successfully imaged a heat plume 3.33a thick, 4a wide and at a depth of 4a.…”
Section: Ert Survey Designmentioning
confidence: 99%
“…Quantitative interpretation remains indeed difficult without additional information, generally in the form of a few additional in situ measurements or/and the use of additional geophysical methods (for instance GPR or induced polarization). Electrical resistivity tomography (ERT) has proven its efficiency to image and/or monitor spatial phenomena [43] such as salt water intrusions [44,45], variations in moisture content (e.g., [46,47]), biodegradation of hydrocarbons (e.g., [48,49]) and salt tracer experiments (e.g., [50,51] and references therein). An in-depth review of electrical properties of rocks can be found in Schön [52] or Revil et al [53], whereas a description of electrical methods can be found in Binley and Kemna [54].…”
Section: Electrical Resistivity Tomographymentioning
confidence: 99%
“…Among them, the Electrical Resistivity Tomography (ERT) is considered as one the most efficient techniques in imaging such properties and processes associated to subsurface geoelectrical structure (Daily et al, 1992;Park, 1998;Muller et al, 2003;Singha and Gorelick, 2005;Mohnke et al, 2006;Nguyen et al, 2009). In order to eliminate limitations of resolution decrease with increasing depth of investigation, ERT techniques based on variations of borehole, surface-to-borehole and cross-hole measurements, have been proposed (Asch and Morrison, 1989;Daily and Owen, 1991;Slater et al, 2000;Zhou and Greenhalgh, 2000;Friedel et al, 2004;Marescot et al, 2002;Tsourlos et al, 2004Tsourlos et al, , 2005Wilkinson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%